Empowering Mengwitani Village Community through processing used cooking oil into eco-friendly solid soap - Dewa Ayu Anom Yuarini; I Gede Arie Mahendra Putra; Putu Julyantika Nica Dewi; M. Habib Arif Budiman; Carolline Octovinarti Ina Kasi Langkeru; Made Satria Wibawa; Ni Kadek Pingkan Wulandari (University of Merdeka Malang, 2025)
Used cooking oil, commonly produced from household cooking activities, poses serious risks to health and the environment if used repeatedly or disposed of carelessly. Repeated heating causes the formation of harmful compounds such as free fatty acids, aldehydes, and acrolein, while disposal into waterways can cause significant pollution. This community service program aims to enhance the knowledge and skills of housewives in Banjar Adat Taman Sari, Mengwitani Village, in processing used cooking oil into useful products, particularly solid soap. The activity conducted on July 24, 2025, employs a participatory learning-by-doing approach through interactive presentations and hands-on practice. Participants were introduced to the hazards of used cooking oil, purification techniques using activated carbon, and soap-making methods. Out of 37 participants, 4–6 was directly involved in the practical session, while the others followed via a live stream. The soap produced met the standards for cold-process soap in terms of color, scent, and texture. The program successfully raised environmental awareness, empowered women with practical skills, and opened up opportunities for household-scale businesses based on environmentally friendly practices.